PLBSD: a Platform for Proactive Location-based Service Discovery - Niforatos, Evangelos; Karapanos, Evangelos; Sioutas, Spyros (My University, 2012)
We introduce a platform for the rapid prototyping of proactive location-based service discovery, proactive location-based services are conceptualised along three broad categories: location-triggered services chain-triggered services, proximity-triggered services, and illustrated through a number of usage scenarios. We report on a workshop with designers and researchers in the area of location-based services that resulted in a set of initial requirements for the platform. We describe how the platform aims at addressing these requirements, and illustrate the implemented features through the development of a proactive location-based application.
Keywords: Application prototyping; Discovery; Location-based services; Platform; Proactive